Brenner tumour of the vagina. Issue 7 (July 1995) - Rashid, A M; Fox, H
Abstract : Polyps of the vagina are rare and are either of inflammatory/reactive or neoplastic origin. A case of extraovarian Brenner tumour of the vagina in a postmenopausal woman, who presented with a vaginal polyp, is described. The polyp was excised and on histological examination, had the triphasic pattern (transitional, glandular and stromal) characteristic of Brenner tumour. The histogenesis of Brenner tumour is discussed in the context of this unusual location and the controversy of its origin.